Efficacy of repeated balloon venoplasty for treatment of hepatic venous outflow obstruction after pediatric living‐donor liver transplantation: A single‐institution experience. (18th June 2019) - Shimata, Keita; Sugawara, Yasuhiko; Honda, Masaki; Ikeda, Osamu; Tamura, Yoshitaka; Hayashida, Shintaro; Ohya, Yuki; Yamamoto, Hidekazu; Yamashita, Yasuyuki; Inomata, Yukihiro; Hibi, Taizo
Abstract: HVOO is a rare complication after LT and an important cause of graft failure. Balloon venoplasty is the first‐line treatment for HVOO, but the effect of repeated balloon venoplasty and stent placement for HVOO recurrence after pediatric LDLT remains unclear. Between 1998 and 2016, 147 pediatric patients underwent LDLT in our institution. Among them, the incidence of HVOO and the therapeutic strategy were retrospectively reviewed. Ten patients were diagnosed with HVOO. All the patients underwent LLS grafts. Median age at the initial endovascular intervention was 2.7 years (range, 5 months‐8 years). The median interval between the LDLT and the initial interventional radiology was 2.7 months (range, 29 days‐35.7 months). Four patients experienced no recurrence after a single balloon venoplasty; 6 underwent balloon venoplasty more than 3 times because of HVOO recurrence; and 2 underwent stent placement due to the failure of repeated balloon venoplasty. All patients are alive with no symptoms of HVOO. The HVOO recurrence‐free period after the last intervention ranged from 20 days to 15.5 years (median, 8.9 years). Repeated balloon venoplasty may prevent unnecessary stent placement to treat recurrent HVOO after pediatric LDLT.